THE ROLE OF SOCIAL MEDIA INFLUENCERS IN PROMOTING STEM AWARENESS AND POLICY REFORM: A SOCIAL NETWORK ANALYSIS APPROACH - Wee-Ling Tan; Mohd Ali Samsudin, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
STEM fields are the driving force in advancing society and providing opportunities for personal and professional growth, from medical breakthroughs to new transportation methods. STEM fields are crucial in innovations and technological advancements that have improved our lives. As the world changes and new challenges arise, the importance of STEM education and careers will only grow. By now, STEM topics are widely discussed on Twitter. Use Twitter to share worldwide news, research, and insights about STEM fields. Therefore, this study aims to discuss online interaction, social networks, and perspectives twitters on STEM fields and even the women in STEM from conversations on Twitter by analyzing the Twitter data. The NodeXL Pro software was used to visualize the network visualization on network participation, especially women in STEM education, within Twitter data. The betweenness centrality to identify the top influencer in STEM conversation on Twitter. The top words in a tweet, the top 10 hashtags, and the most mentioned words on STEM were identified. The research findings demonstrated the existence of higher measures of connection and interaction with others on Twitter. Hence, a better comprehension is needed to understand the power of social media; tended to interact more frequently with all students than most participants from specialist backgrounds.